The Role of Students' Emotional Intelligence: Empirical Evidence - Natalio Extremera Pacheco; Pablo Fernández-Berrocal (Universidad Autónoma de Baja California, 2004)
Emotional intelligence (EI) has attracted great interest in the field of education as a vehicle to improve the socioemotional development of students. The first publications that appeared made a great number of claims about the positive influence of emotional intelligence in the classroom. The only problem was that not all these claims were coupled with empirical research to show, on the one hand, the predictive level of EI, and on the other hand, the actual role of EI in different areas of life. It has been only recently that the effect of a high level of EI exercises on people has been investigated. The object of this article is to examine the most relevant empirical research done within the educational setting, in order to collect the existing evidence for the influence of EI, evaluated by different instruments, in the personal, social and scholastic functioning of students.